2014
DOI: 10.1128/aem.00044-14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence of Bradyrhizobium Strains Nodulating Soybeans as Revealed by Multilocus Sequence Analysis of Genes Inside and Outside the Symbiosis Island

Abstract: The genus Bradyrhizobium has been considered to be a taxonomically difficult group. In this study, phylogenetics and evolutionary genetics analyses were used to investigate divergence levels among Bradyrhizobium strains nodulating soybeans in China. Eleven genospecies were identified by sequence analysis of three phylogenetic and taxonomic markers (SMc00019, thrA, and truA). This was also supported by analyses of eight genes outside the symbiosis island ("off-island" genes; SMc00019, thrA, truA, fabB, glyA, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
5
15
0
Order By: Relevance
“…Aligned sequences from the selected genes were concatenated and 3120 bp positions were obtained (Table S5). The housekeeping genes gyrB , recA and glnII have been used widely in phylogenetic studies of Ensifer strains, while, recently, the core genes truA , thrA and SMc00019 were demonstrated to produce phylogenies congruent with the reference species tree of rhizobia . The discriminatory power of the selected gene sequences used for the Ensifer taxa was estimated by the number of parsimony‐informative sites contained in each gene (Table S5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aligned sequences from the selected genes were concatenated and 3120 bp positions were obtained (Table S5). The housekeeping genes gyrB , recA and glnII have been used widely in phylogenetic studies of Ensifer strains, while, recently, the core genes truA , thrA and SMc00019 were demonstrated to produce phylogenies congruent with the reference species tree of rhizobia . The discriminatory power of the selected gene sequences used for the Ensifer taxa was estimated by the number of parsimony‐informative sites contained in each gene (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…The housekeeping genes gyrB, recA and glnII have been used widely in phylogenetic studies of Ensifer strains, 49 -52 while, recently, the core genes truA, thrA and SMc00019 were demonstrated to produce phylogenies congruent with the reference species tree of rhizobia. 31,53,54 The discriminatory power of the selected gene sequences used for the Ensifer taxa was estimated by the number of parsimony-informative sites contained in each gene (Table S5). In our analysis, SMc00019 had the greatest percentage of parsimony-informative characters (31.5%), of the positions used, followed by truA (31.5%), gyrB (30.3%), glnII (29.2%), thrA (26.7%) and recA (23.5%).…”
Section: Multi-locus Sequence Analysis Of Housekeeping Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…As several studies reported a congruent phylogeny among nodulation genes and nifH (45)(46)(47), the latter was regarded to be representative. The final alignment consisted of 286 nucleotides, and the Tamura 3-parameter model with gammadistributed evolutionary rates among sites (T92 ϩG) was the bestfit model according to MODELTEST analysis.…”
Section: Isolation Of Root Nodule Rhizobia From the Okavango Regionmentioning
confidence: 99%